1962
DOI: 10.2134/agronj1962.00021962005400010016x
|View full text |Cite
|
Sign up to set email alerts
|

Root and Top Growth of Corn1

Abstract: Synopsis Root growth was found to occur in a series of stages which caused roots to appear in different locations of the soil at different times. Root growth stages were associated with stages of top growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 1 publication
7
40
0
2
Order By: Relevance
“…However, most root studies have used this technique, although comprehensive studies have not often been attempted. Root dry matter yield (Table 2) represented about 10% of the total, which agrees with the data of Weihing (1935), Foth (1962), and van Eijnatten (1963) and suggests that roots may have an important influence on sourcesink patterns during growth and development and thus warrant further detailed study. As might be expected, the amount and rate of N uptake by the maize plants varied with the amount of N available to the root systems (Table 4), which was also reflected in the concentrations in the plant components.…”
Section: Discussionsupporting
confidence: 84%
“…However, most root studies have used this technique, although comprehensive studies have not often been attempted. Root dry matter yield (Table 2) represented about 10% of the total, which agrees with the data of Weihing (1935), Foth (1962), and van Eijnatten (1963) and suggests that roots may have an important influence on sourcesink patterns during growth and development and thus warrant further detailed study. As might be expected, the amount and rate of N uptake by the maize plants varied with the amount of N available to the root systems (Table 4), which was also reflected in the concentrations in the plant components.…”
Section: Discussionsupporting
confidence: 84%
“…Com root distribution in loam and sandy loam soils in Michigan (Foth, 1962), and in a silt loam soil in Illinois (Fehrenbacher and Alexander, 1955) have been described. Additional field studies of corn rooting systems have been limited to measuring root weights at certain row or interrow positions (Barber, 1971;Mayaki et al, 1976;Kaspar et al, 1991) or root length densities (Raczkowski, 1988;Vepraskas and Hoyt, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Ocamb and Kommedahl (1994) reported that F. moniliforme survived most readily in soil to a depth of 30 cm, and survival increased from the soil surface to that depth. Most seedlings collected in our study were in végétative stage 1 as defined by Foth (1962). Since ail samples were removed and inspected from 3 to 28 d after planting, seedling roots were within the zone of reportedly high concentration of F. moniliforme.…”
Section: Discussionmentioning
confidence: 99%